The magnitude of crop yield improvement with different soil acidity management practices in the Ethiopian highlands: a meta-analysis - Birhanu, Agumas; Desta, Gizaw; Agegnehu, Getachew; Legesse, Gizachew; Feyisa, Tesfaye; Sileshi, Gudeta Weldesemayat (CSIRO Publishing, 2025)
Soil acidity affects over 44% of Ethiopia’s farmland, yet knowledge of acid soil management practices (ASMPs) and their impact on crop yields remains limited. Quantitative syntheses of studies on ASMPs and their role in yield improvement are also lacking in Ethiopia. This meta-analysis aimed to: (1) compile datasets to estimate yield improvements from ASMPs; and (2) provide a quantitative synthesis for evidence-based acid soil management in the Ethiopian highlands. Meta-analysis of 30 experiments across 48 locations with pH < 5.5 was conducted to quantify ASMP effects on crop yields. Linear mixed-effects model was applied using the response ratio (RR), calculated using treatment yield to respective no-input control. Sub-group analyses quantified variability within and between ASMPs. The weighted mean RR was 1.67 indicating that implementing ASMPs can increase yield by 67% relative to the control. However, significant residual heterogeneity (I2 = 98%, τ2 = 0.37) was also noted. Lime + phosphorus (P) fertiliser achieved the highest yield increase (RR = 2.94), followed by P fertiliser alone (RR = 1.60) and lime alone (RR = 1.36). Sub-group analysis revealed greater yield increases following compost + N (RR = 2.48), biochar + compost + N (RR = 2.29), biochar + N (RR = 2.25), biochar + compost (RR = 1.55), biochar alone (RR = 1.51), farmyard manure (FYM) (RR = 1.49), and FYM + P + N (RR = 1.28) relative to the control. It is concluded that implementing ASMPs increases crop yields by 28–194% relative to the control. Compared to the other ASMPs, lime + P achieved significantly higher yield increases across all agroecological zones, soil texture and slope classes. These findings emphasize ASMPs’ potential to enhance crop production in Ethiopia, providing valuable guidance for effective acid soil management policies and practices.